2022
DOI: 10.1097/bot.0000000000002422
|View full text |Cite
|
Sign up to set email alerts
|

Do Intrawound Antibiotics Reduce the Incidence of Surgical Site Infections in Pelvic and Lower-Limb Trauma Surgery? A Systematic Review and Meta-analysis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…More recently, several authors have suggested the utility of topical antibiotics in extremity trauma. Multiple systematic reviews and meta-analyses noted improvement in infection rates in patients with fractures when topical antibiotics were applied intraoperatively, although a variety of topical agents were used 26–30 . Most of the literature on this comes from orthopedic studies, with a presumption of a sterile or at least clean surgical site and access to prompt surgical intervention, but several studies have specifically investigated topical vancomycin in combat trauma with demonstrated benefit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, several authors have suggested the utility of topical antibiotics in extremity trauma. Multiple systematic reviews and meta-analyses noted improvement in infection rates in patients with fractures when topical antibiotics were applied intraoperatively, although a variety of topical agents were used 26–30 . Most of the literature on this comes from orthopedic studies, with a presumption of a sterile or at least clean surgical site and access to prompt surgical intervention, but several studies have specifically investigated topical vancomycin in combat trauma with demonstrated benefit.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple systematic reviews and meta-analyses noted improvement in infection rates in patients with fractures when topical antibiotics were applied intraoperatively, although a variety of topical agents were used. [26][27][28][29][30] Most of the literature on this comes from orthopedic studies, with a presumption of a sterile or at least clean surgical site and access to prompt surgical intervention, but several studies have specifically investigated topical vancomycin in combat trauma with demonstrated benefit. The suggested benefits include MRSA coverage, high concentration of antibiotic at the site of infection, negligible systemic side effects, and low cost.…”
Section: Extremity Traumamentioning
confidence: 99%